Public Reading In Improving The Ability To Read, Write, Count (Calistung) In Sunday Learning - Alviansyah, Muhammad Rafli; Karwati, Lilis; Novitasari, Nastiti (Universitas Negeri Padang, 2024)
The problems faced by parents towards their children who have difficulty in providing an understanding of learning in school, so there must be an effort, one of which is through the Sunday Teaching Program initiated by the Community Reading Gardens to improve learning skills in reading, writing and counting (Calistunng). The purpose of this research is to find out the efforts of Taman Bacaan Masyarakat in improving children's literacy and numeracy. The method used in this research is qualitative with descriptive approach. Data collection techniques through observation interviews and documentation. The results of the field findings that the Baitul Mu'minin Community Reading Garden (TBM) in an effort to improve reading, writing and counting skills (calistung) in children through the Sunday Teaching program carry out interesting activities ranging from: (1) activities to read books one sheet per session, (2) free tutoring, (3) attracting children's interest in reading by reading books together, then the book is read by the tutor, (4) creating a comfortable and pleasant learning atmosphere, through the use of learning media, (5) as well as a varied collection of reading books so as to attract children's interest in learning. TBM Baitul Mu'minin handles learning activities with a playful approach and becomes an alternative choice for the community, especially parents, to help their children improve their learning skills. In conclusion, the efforts of community reading garden in improving calistung, the results can help children improve their ability to read, write, count better and increase.